Kegiatan Pengabdian Masyarakat dalam Edukasi Penyakit Dislipidemia serta Komplikasinya terhadap Penyakit Kardiovaskular - Catharina Sagita Moniaga; Jasmine Syabania Noviantri; Giovanno Sebastian Yogie; Yohanes Firmansyah; Hendsun Hendsun (Jurnal Kabar Masyarakat, 2023)
Coronary heart disease occurs when the blood vessels that supply blood to the heart are blocked by plaque build up in the walls of the blood vessels. Uncontrolled dyslipidemia can lead to faster plaque build up and a higher risk of having a heart attack. Community service activities are important to increase public awareness of dyslipidemia and coronary heart disease for early detection before complications occur. Community service activities were carried out at the Kalam Kudus II Jakarta Foundation involving 52 respondents. Activities carried out in the form of community education, physical and supporting examinations, and counseling. The results showed that 6 (11.5%) respondents had high total cholesterol and high LDL levels, 37 (71.2%) respondents had low HDL levels, 8 (15.4%) respondents had high triglyceride levels, and 8 (15.4%) of respondents diagnosed with suspected coronary heart disease based on examination of the electrocardiogram. Early detection is an effort to detect the presence of cardiovascular disease and dyslipidemia at an early stage so that action can be taken immediately to prevent more serious conditions. Education and early detection of cardiovascular disease and dyslipidemia are very important to prevent more serious diseases from occurring in the future. Through appropriate counseling and early detection, it is hoped that the public will be more aware of the importance of maintaining health and preventing cardiovascular disease and dyslipidemia.